Platelet-to-high-density lipoprotein cholesterol ratio as a predictor of stroke risk: a longitudinal analysis of the China health and retirement longitudinal study - Feng, Qilin; Ren, Liuying; Chen, Sijiang; Li, Xiaoqiang (Frontiers in Neurology, 2025)
BackgroundStroke is a major health concern in aging populations. This study investigates the platelet-to-high-density lipoprotein cholesterol ratio (PHR) as a predictor of stroke risk in middle-aged and older Chinese adults.MethodsWe analyzed data from 8,405 participants aged ≥45 years in the China Health and Retirement Longitudinal Study (CHARLS), with an 8-year follow-up. PHR was calculated from baseline blood samples. Multivariate logistic regression models, supplemented by smooth curve fitting to assess dose–response relationships and subgroup analyses with interaction testing, assessed the association between PHR and stroke incidence, adjusting for various factors.ResultsDuring follow-up, 753 (8.96%) participants reported a stroke. Smooth curve fitting visually confirmed a linear dose–response relationship between PHR and stroke probability. Each standard deviation increase in PHR was associated with 17% higher odds of stroke (OR: 1.17; 95% CI: 1.08–1.26, p < 0.05). The highest PHR quartile had 42% higher odds of stroke compared to the lowest (OR: 1.42; 95% CI: 1.14–1.76, p = 0.002), with a significant trend across quartiles (p < 0.05).ConclusionElevated PHR is independently associated with increased stroke risk in middle-aged and older Chinese adults. Incorporating PHR into existing risk assessment tools may enhance stroke risk stratification and guide preventive strategies. Further research is needed to elucidate underlying mechanisms and validate findings in diverse populations.